1996
DOI: 10.1161/01.cir.93.10.1860
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Endothelin Receptor Blockade Decreases Peripheral Vascular Resistance and Blood Pressure in Humans

Abstract: The endothelin ETA/B receptor antagonist TAK-044 decreases peripheral vascular resistance and, to a lesser extent, blood pressure; increases circulating endothelin concentrations; and blocks forearm vasoconstriction to exogenous endothelin-1. These results suggest that endogenous generation of endothelin-1 plays a fundamental physiological role in maintenance of peripheral vascular tone and blood pressure. The vasodilator properties of endothelin receptor antagonists may prove valuable therapeutically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
155
2
11

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(183 citation statements)
references
References 42 publications
15
155
2
11
Order By: Relevance
“…These results are consistent with prior reports that endothelin makes important contributions to the regulation of systemic blood pressures, [6][7][8] and suggest that endothelin's contributions to altered regulation of peripheral vascular function also have an impact on elevated blood pressure particularly in DM2. The specific effect observed in diabetic subjects on pulse pressure reflects a proportionally greater reduction in systolic than diastolic pressure.…”
supporting
confidence: 92%
“…These results are consistent with prior reports that endothelin makes important contributions to the regulation of systemic blood pressures, [6][7][8] and suggest that endothelin's contributions to altered regulation of peripheral vascular function also have an impact on elevated blood pressure particularly in DM2. The specific effect observed in diabetic subjects on pulse pressure reflects a proportionally greater reduction in systolic than diastolic pressure.…”
supporting
confidence: 92%
“…Because the venous system may contribute to the high cardiac output observed in early phases of hypertension, ET-1 may play a role at this stage of the disease. 13,22 Therefore, our finding of altered receptor profile in the saphenous veins of hypertensive patients is relevant regarding the pathogenesis of hypertension in African American patients. Results of the present study provided evidence that in addition to ET-1 expression, ET receptors are also differentially regulated in African Americans and may be important for the development and/or maintenance of hypertension in this population.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to the effects of ET-1 on arteries, ET-1-mediated constriction in the venous system is enhanced in hypertensive patients. 22 Haynes et al 22 studied the responses to local infusion of ET-1 into hand veins and found that maximal contraction in response to ET-1 was significantly greater in the hypertensive group than in the normotensive group. Furthermore, ET-1 potentiated sympathetically mediated vasoconstriction in hypertensive patients, and a positive correlation was observed between ET-1-induced venoconstriction and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Analogous observations have been made for the control of total peripheral resistance, which is diminished by ET A and increased by ET B blockers. [60][61][62] The relative quantitative contribution of these two components to the regulation of normal BP has not been established. In essential hypertension, vasoconstriction of regional (forearm) vascular beds by ET A seems to be enhanced, 58,59 and dilation by ET B abolished or reversed.…”
Section: Endothelins and Bp Regulationmentioning
confidence: 99%